The total phenolic and flavonoid contents of Aloe vera and Morinda citrifolia extracts as antibacterial material against Pseudomonas aeruginosa. (2023) - Royani, Ahmad; Hanafi, Muhammad; Julistiono, Heddy; Manaf, Azwar
Abstract: Pseudomonas aeruginosa is a pioneer bacterium initiating the biofilm formation process so that it is corrosive to some metals in the marine environment. One of the efforts to prevent and control corrosion due to environmentally friendly biofilms is using green biocides. The extraction of Aloe vera and Morinda citrifolia with methanol were carried out to obtain antibacterial material. The extract of those plants with multilevel maceration method. The study aimed to identify the total phenolic and flavonoid contents in A. vera and M. citrifolia crude extracts and compare the two antibacterial extract activities. The total phenolic and flavonoid contents were analyzed using the Folin-Ciocalteu and the aluminum chloride colorimetric methods. The antibacterial activity against P. aeruginosa was conducted using the microdilution method to determine the minimum inhibitory concentration (MIC). The structure of the bioactive components of both A. vera and M. citrifolia extracts were identified using a liquid chromatography-mass spectrometer (LC/MS-MS). The MIC of A. vera and M. citrifolia for P. aeruginosa bacteria is about 6144 µg/mL, while the MIC of antibiotic Enrofloxacin is 16 µg/mL. The mean of total phenolic and flavonoid contents for the methanolic extracts of A. vera and M. citrifolia were 1.39% and 4.03% (phenolic), and 0.26% and 0.28% (flavonoids), respectively. The chemical structure of A. vera consists of 2″-O-Feruloylaloesin, Kaempferol-3-O-rutinoside, and Natsudaidain. At the same time, the chemical structure of M. citrifolia consists of 7-Hydroxy-Methoxycoumarin and Cirsiumaldehyde. A. vera and M. citrifolia crude extracts had lower inhibition than antibacterial control (Enrofloxacin) for P. aeruginosa . The lower bacteria inhibition was due to the low active materials (phenolic and flavonoid contents). So, the purification methods of crude extracts to obtain active materials with high antibacterial activity were needed.